Characteristics of Toxocara canis induced lung inflammation in C57BL/6 mice - Lekki-Jóźwiak, Janina; Karabowicz, Justyna; Paschall, Magdalena; Gregorczyk-Zboroch, Karolina; Sobczak-Filipiak, Małgorzata; Bąska, Piotr; Schabussova, Irma; Długosz, Ewa (Frontiers in Immunology, 2025)
Toxocariasis, a neglected zoonotic disease caused by parasites of the Toxocara genus, represents a significant public health concern, with an estimated global seroprevalence of 19%. Despite the well-known respiratory symptoms associated with toxocariasis, the immune response in the lungs during toxocariasis is still poorly understood. This study analyzes both local lung and systemic immune response to T. canis infection and T. canis excretory-secretory antigens (TES) intranasal application in C57BL/6J mice. Lungs, blood, and spleens were collected at specific time points for histopathological analyses, flow cytometry, cytokine profiling, and gene expression studies. The systemic immune response was further assessed by cytokine measurements in splenocyte cultures and the detection of TES-specific antibodies. T. canis infection triggered severe pulmonary inflammation characterized by eosinophilia and mucus accumulation, with persistent inflammation lasting up to 28 days post-infection. Interestingly, this response was not solely driven by Th2-type interleukin production. Cytokine analysis of splenocyte cultures revealed elevated levels of IL-5 and IL-6, along with increased TES-specific IgE and IgG1 antibody concentrations. In contrast, TES application alone induced local eosinophil infiltration and upregulated genes associated with lung repair, though this response was less intense and shorter-lived compared to the infection. Our study is the first to present a comprehensive cytokine proteome analysis in mouse lungs during T. canis infection and stimulation by larval antigens, highlighting the key role of cytokines such as IL-5, IL-6, and IL-33. These findings provide new insights into the pathogenesis of toxocariasis and underscore the need for further research into potential therapeutic targets.